2022
DOI: 10.3389/fimmu.2022.1041284
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic gene signatures and aberrant pathway activation based on m6A methylation regulators in rheumatoid arthritis

Abstract: PurposeRheumatoid arthritis (RA) is a chronic autoimmune disease (AD) characterized by persistent synovial inflammation, bone erosion and progressive joint destruction. This research aimed to elucidate the potential roles and molecular mechanisms of N6-methyladenosine (m6A) methylation regulators in RA.MethodsAn array of tissues from 233 RA and 126 control samples was profiled and integrated for mRNA expression analysis. Following quality control and normalization, the cohort was split into training and valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Several studies have investigated the role of IGF2BP3 in modulating macrophage phenotype, while the results have been conflicting. Some researchers claimed that IGF2BP3 promotes proinflammatory M1 macrophage polarization, while others deemed it to enhance M2 subtype shifting [ 80 , 81 ]. In our study, we found IGF2BP3 overexpressed BMDMs polarized into the M1 phenotype and secreted more inflammatory cytokines, whereas IGF2BP3 knockdown led to M2 polarization and inhibited inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the role of IGF2BP3 in modulating macrophage phenotype, while the results have been conflicting. Some researchers claimed that IGF2BP3 promotes proinflammatory M1 macrophage polarization, while others deemed it to enhance M2 subtype shifting [ 80 , 81 ]. In our study, we found IGF2BP3 overexpressed BMDMs polarized into the M1 phenotype and secreted more inflammatory cytokines, whereas IGF2BP3 knockdown led to M2 polarization and inhibited inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Ni et al analyzed the expression levels of 23 m6A regulators in OA chondrocytes and identified YTHDF3 and IGF2BP3 as upregulated m6A readers in OA chondrocytes and may be correlated with enhanced chondrocyte ECM catabolism [ 30 ]. Zhao et al found that IGF2BP3 is enhanced in the synovium of patients with RA and is a potential regulator of inflammation-related pathways [ 80 ]. Xiong et al identified 12 differentially expressed m6A genes in the OA synovium based on RNA-seq data from 10 normal and 10 OA samples, including IGF2BP3 [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings provide novel sights for developing clinical treatment strategies targeting METTL3, METTL14 and ALKBH5. In addition, through systemically analyzing the roles of m6A modifications in RA based on gene expression profiling data, novel targets were identified for RA clinical diagnosis and therapy, such as, Geng et al found that IGF2BP3 and YTHDC2 could be used to diagnose RA accurately [ 112 ]. Besides, WTAP was involved in the m6A modification of ETS1 and regulated the macrophage polarization progression in RA [ 113 ].…”
Section: M6a and Skeletal System Diseasementioning
confidence: 99%
“…In RA FLS, siIGF2BP3 decreased the expression of cyclin B1 (CCNB1) and cellular myelocytomatosis viral oncogene (c-Myc). IGF2BP3 can regulate the G2/M transition, promote the proliferation of RA FLS, and affect the polarization of M1 macrophages [ 38 ]. However, it remains to be confirmed how IGF2BP3 regulates macrophage polarization and inflammatory deterioration during RA progression through CCNB1 and c-Myc.…”
Section: M6a Methylation In Ramentioning
confidence: 99%
“… [ 37 ] RA IGF2BP3 Reader Synovial tissues Up-regulation Regulates the G2/M transition and affects the polarization of M1 macrophages. [ 38 ] RA SMOC2 - Synovial tissues Up-regulation Controls MYO1C expression through ALKBH5-mediated m6A modification. [ 40 ] RA METTL3 Writer PBMC Up-regulation Attenuated LPS-induced inflammatory response in macrophages via the NF-κB signaling pathway.…”
Section: M6a Methylation In Other Autoimmune Diseasesmentioning
confidence: 99%